2015
DOI: 10.1159/000381525
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Role of Anticholinergic Activity in a Mood Disorder

Abstract: We report a case of a 54-year-old woman presenting with amnesia, apathy, work-related difficulties and mental stress. At presentation, her Mini-Mental State Examination score was 27 and her serum anticholinergic activity (SAA) was positive without medication or recent physical illnesses. In addition, magnetic resonance imaging revealed mild atrophy of the frontal and temporal lobes, with a relatively intact hippocampus. Consequently, we diagnosed mild cognitive impairment due to Alzheimer's disease and prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Some antidepressants, including many SSRIs and tricyclic antidepressants (TCAs), have been shown to inhibit acidic sphingomyelinase (aSMase), an enzyme responsible for catalyzing the breakdown of sphingomyelin to ceramide and phosphorylcholine, resulting in decreased ceramide concentrations (Kornhuber et al, 2010). Use of antipsychotics was also an exclusion criterion due to their effects on mood and cognitive outcomes, as well as their potential effects on sphingolipid concentrations (Alexander, Gallagher, Mascola, Moloney, & Stafford, 2011;Hori et al, 2015;Kornhuber, Tripal, Gulbins, & Muehlbacher, 2013;Kornhuber et al, 2008). Patients diagnosed with any dementia, Parkinson's disease, Huntington's chorea, an autoimmune disease (e.g., multiple sclerosis, rheumatoid arthritis, Crohn's disease), active cancer, impaired liver or kidney function, or history of cerebrovascular accident (CVA), transient ischemic attack (TIA), brain tumor, subdural hematoma, epilepsy, or any other conditions likely to significantly impact mood or cognition were excluded from this study.…”
Section: Participantsmentioning
confidence: 99%
“…Some antidepressants, including many SSRIs and tricyclic antidepressants (TCAs), have been shown to inhibit acidic sphingomyelinase (aSMase), an enzyme responsible for catalyzing the breakdown of sphingomyelin to ceramide and phosphorylcholine, resulting in decreased ceramide concentrations (Kornhuber et al, 2010). Use of antipsychotics was also an exclusion criterion due to their effects on mood and cognitive outcomes, as well as their potential effects on sphingolipid concentrations (Alexander, Gallagher, Mascola, Moloney, & Stafford, 2011;Hori et al, 2015;Kornhuber, Tripal, Gulbins, & Muehlbacher, 2013;Kornhuber et al, 2008). Patients diagnosed with any dementia, Parkinson's disease, Huntington's chorea, an autoimmune disease (e.g., multiple sclerosis, rheumatoid arthritis, Crohn's disease), active cancer, impaired liver or kidney function, or history of cerebrovascular accident (CVA), transient ischemic attack (TIA), brain tumor, subdural hematoma, epilepsy, or any other conditions likely to significantly impact mood or cognition were excluded from this study.…”
Section: Participantsmentioning
confidence: 99%
“…However, at the pathological state (depressive state), more upregulation of ACh is not impossible because the ChAT activity is already upregulate. Therefore, in depression there might be a possibility of endogenous appearance of AA [14]. In delirium, we also speculate there might be a possibility of the appearance of AA in delirium.…”
Section: Opinionmentioning
confidence: 78%
“…Consistent with our previous results, the present study confirmed that OBX mice exhibit long-term memory-related behavioral impairments in the passive avoidance test, 14 d after the surgery. 13,23) We demonstrated that the administration of Dyn A or trans-(−)-U-50488 improved the cognitive deficits of OBX mice, and this effect was significantly inhibited by pre-administration of the κ-opioid receptor antagonist nor-BNI. These results are consistent with the findings of a previous study that used a rat model of memory deficits, induced by the muscarinic acetylcholine receptor antagonist scopolamine.…”
Section: Discussionmentioning
confidence: 92%
“…Step-Through Passive Avoidance Task The passive avoidance test was performed as previously described. 13,23) In the training trial, before the OBX surgery, each mouse was placed in the illuminated compartment and the latency to enter the dark compartment was recorded. As soon as the mouse had completely moved from the lighted compartment into the dark compartment, an electric foot-shock (1 mA for 500 ms) was delivered through the floor grids.…”
Section: Methodsmentioning
confidence: 99%